Observation for the feasibility of a bile duct biopsy technique using a loop-tip guidewire during endoscopic retrograde cholangiopancreatography. Issue 41 (14th October 2022) - Lee, Kang Won; Lee, Jae Min; Choi, Hyuk Soon; Kim, Eun Sun; Keum, Bora; Jeen, Yoon Tae; Chun, Hoon Jai; Lee, Hong Sik
Abstract : Endoscopists frequently have difficulty approaching biliary lesions using biopsy forceps. The aim of this study was not only to describe an easy technique for biliary biopsy assisted by a looped guidewire but also to present preliminary results regarding its safety and feasibility. A preliminary proof-of-concept study was performed at a single tertiary medical center. Between August 2019 and January 2020, 13 patients with bile duct strictures underwent endoscopic retrograde cholangiopancreatography (ERCP) with a new loop guidewire-assisted forceps approach technique. The efficacy and safety were evaluated using the success rate as the primary outcome and diagnostic yield and complication rates as secondary outcomes. The tissue sampling success rate was 100% (13/13). All samples were acceptable for histopathological analysis. Eleven specimens were confirmed to be adenocarcinomas. After reexamination of the remaining 2 patients, all cases were eventually diagnosed as being malignant. The sensitivity of the single procedure was 84.6% (11/13). There were 2 patients with mild hyperamylasemia, but there were no severe complications with respect to safety. This new technique could enhance the success rate and diagnostic yield and reduce the risk of failure when using the biopsy forceps approach during ERCP.